The Influence of Social Media on the Reduced Politeness of Language in Adolescents - Dewa Ayu Kartika Prasanti (Universitas Nurul Jadid, 2023)
This research is motivated by data showing the influence of social media on language politeness in adolescents. The objectives to be achieved in this study include: (1) Knowing whether social media has an effect on adolescent politeness in language through public perception (2) Knowing how social media influences adolescent language politeness (3) providing references for readers regarding the study of the influence of social media and language politeness. This research was conducted through a survey that was distributed through social media and had the participation of 45 people. The results of the study show how social media has an effect on reducing politeness in language in adolescents. From the data obtained, it can be recommended to the audience that social media can have an effect on adolescent language politeness.